Sistem Informasi Penilaian Guru Di Madrasah Aliyah Negeri 1 Selat Panjang - Zulfikri Zulfikri (Prodi Sistem Informasi Universitas Dharma Andalas, 2022)
Madrasah Aliyah Negeri (MAN) 1 Meranti Islands is one of the schools that has implemented Teacher Performance Assessment (PKG) to ensure the quality of learning and promotion of teachers. The lack of use of Information Technology (IT) in supporting the PKG data processing process causes the assessment process to be complicated with inaccurate results. The use of programming languages ​​that are connected to the database will certainly speed up and simplify the PKG data processing process. The final result of this research is the design of the PKG information system at MAN 1 Kepulauan Meranti using the Visual Basic 6.0 programming language and SQL Server 2005 database. By using the PKG information system, the PKG value calculation process becomes faster and more precise, the value recap process and creation PKG reports also become more practical.